Kajian Literatur: Penerapan Big Data dan Artificial Intelligence untuk Perkembangan Bidang Edukasi dan Bisnis - Sunarto, Shilvy Andini; Maulidina, Citra Puspa; Wijaya, Widiastiana Vista (Kinesik, 2024)
Big Data and AI (Artificial Intelligence) are the results of technological developments that can be enjoyed today. Big Data and AI are very helpful in the development of education and the business world. The purpose of this paper is to look at and analyze related literature studies on the application of Big Data and AI Communication in the field of education and the business world. This writing uses the literature review method from the Google Scholar online database. Four international journals related to Big Data and AI have been curated. The results of the journal literature review that have been analyzed show that Big Data and AI are closely related and help in the development of the education field and the business world such as making advertisements, post Covid-1 interactive learning, and can analyze important issues to create business value through Big Data analysis. So that the application and integration of Big Data and AI is a great opportunity to increase efficiency and effectiveness in various fields, especially in education and the business world.